PENGARUH PROMOSI DAN KELOMPOK REFERENSI TERHADAP KEPUTUSAN MENABUNG NASABAH TABUNGAN SIMPEDES PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK KANTOR CABANG BRIGJEN SUDIARTO SEMARANG - Elsa Wilna; Nawazirul Lubis; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2015)
Promotions and reference groups believed to increase the intensity of saving customers. This study aims to determine how strong the effect of promotions and group reference to saving decision saving customer simpedes at PT. BRI (Persero) Tbk Branch Office Brigjen Sudiarto Semarang. This type of research is explanatory research. The study population was all customers savings simpedes PT. BRI (Persero) Tbk Branch Office Brigjen Sudiarto Semarang in 2013, while the number of samples is set just 100 respondents were selected using incidental sampling technique. Collecting data using interview techniques and research instrument was a questionnaire. Research data analysis using statistical analysis using SPSS for Windows version 16.0.